2006
DOI: 10.1002/jccs.200600144
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Waste Tyres into Carbon Black and their Utilization as Adsorbent

Abstract: Pyrolysis has the potential of transforming used tyres into useful recyclable products. Pyrolytic carbon black is one of the most important products of tyre pyrolysis. Waste tyres were pyrolysed at 450°C in a batch reactor under atmospheric pressure. The recovered pyrolytic carbon black residues were studied to investigate their characteristics for use as a possible adsorbent. EDX elemental analysis and surface area determinations were used to investigate the distinctive features of pyrolytic carbon black. Due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(33 citation statements)
references
References 16 publications
(13 reference statements)
3
28
0
2
Order By: Relevance
“…The high volatility of zinc is exploited practically in the industrial production of metallic zinc, where zinc ore (containing ZnO) is heated in the presence of coke, and metallic zinc evolves as a vapour. We compared our results to another study presented in the literature [10][11][12][13], which confirmed the high zinc content in the bare postpyrolysis char from tires (4.2 wt. %).…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…The high volatility of zinc is exploited practically in the industrial production of metallic zinc, where zinc ore (containing ZnO) is heated in the presence of coke, and metallic zinc evolves as a vapour. We compared our results to another study presented in the literature [10][11][12][13], which confirmed the high zinc content in the bare postpyrolysis char from tires (4.2 wt. %).…”
Section: Resultssupporting
confidence: 75%
“…Table 2 proves that the sulphur content in the investigated char is low. Additionally, our XRD investigations did not reveal the presence of ZnS in the char, as found in other studies [11][12][13]. High content of sulphur (also as ZnS) could considerably limit the utilization of such a sulphur-rich char by combustion.…”
Section: Resultssupporting
confidence: 53%
“…Activated carbon has many applications including water treatment [172,173], chemical and petroleum industries [91], separation, purification [174], catalysis [101,175], energy storage [159], batteries, fuel cells [176], nuclear power stations [177], electrodes for electric double layer capacitors [178], pharmaceutical [163], hydrometallurgy [104,179] and others.…”
Section: Activated Carbon Applicationsmentioning
confidence: 99%
“…The fed tyres are heated up in the absence of oxygen [19]. The process is carried out at a temperature range of 450e500 C. The volatile vapour evolved in the reactor is condensed in a water cooled condenser.…”
Section: Pyrolysis Of Tyresmentioning
confidence: 99%